2022
DOI: 10.20944/preprints202210.0317.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-Wide Characterization of Sulfate Transporter Gene Family in Oilseed Crops: Camelina sativa and Brassica napus

Abstract: Sulfate transporters (SULTRs) are responsible for the uptake of the sulfate (SO42−) ions in the rhizosphere by the roots and their distribution in plant organs. In this study, SULTR family members in the genome of the two oilseed crops, Camelina sativa, and Brassica napus, were identified and characterized based on their sequence structure, duplication events, phylogenetic relationships, phosphorylation sites, and expression levels. Herein, 36 and 45 putative SULTR genes were recognized from the genome of C. s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…The number of copies of a gene can be related to polyploidy events and segmental and tandem duplications [46,47]. Increasing the number of isoforms of a gene can be effective at increasing functional diversity and related interactions [48]. Phylogenetic analysis of C4H proteins revealed that there is a large genetic distance between the C4H genes of monocot and dicot plants, suggesting that they have undergone a different evolutionary process.…”
Section: Discussionmentioning
confidence: 99%
“…The number of copies of a gene can be related to polyploidy events and segmental and tandem duplications [46,47]. Increasing the number of isoforms of a gene can be effective at increasing functional diversity and related interactions [48]. Phylogenetic analysis of C4H proteins revealed that there is a large genetic distance between the C4H genes of monocot and dicot plants, suggesting that they have undergone a different evolutionary process.…”
Section: Discussionmentioning
confidence: 99%